2014
DOI: 10.1007/s10637-014-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and excretion of 14C-lenvatinib in patients with advanced solid tumors or lymphomas

Abstract: Summary Lenvatinib is an orally available multi-targeted tyrosine kinase inhibitor with anti-angiogenic and antitumor activity. To get more insight into the disposition of lenvatinib, a mass balance study was performed in patients with advanced solid tumors. A single oral 24 mg (100 μCi) dose of 14 Clenvatinib was administered to six patients, followed by collection of blood, plasma, urine and feces for 7 to 10 days. The collected material was analyzed for total radioactivity, unchanged lenvatinib and selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 17 publications
3
54
0
1
Order By: Relevance
“…It might depend on the nature of the surgery and, perhaps more importantly, the half-life of each targeted agents. For example, the terminal elimination half-life of lenvatinib was approximately 35 hours [14]. It indicates that lenvatinib is almost washed out from the body after its cessation for 7 days (equivalent to approximately five half-lives).…”
Section: Discussionmentioning
confidence: 99%
“…It might depend on the nature of the surgery and, perhaps more importantly, the half-life of each targeted agents. For example, the terminal elimination half-life of lenvatinib was approximately 35 hours [14]. It indicates that lenvatinib is almost washed out from the body after its cessation for 7 days (equivalent to approximately five half-lives).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of lenvatinib decline bi-exponentially after C max is attained, with a terminal elimination half-life (t ) of *28 h [4]. In patients with solid tumours, *64 % of radioactive lenvatinib was eliminated in the faeces and *25 % in the urine [4,31].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Earlier studies have shown that lenvatinib exposure is neither affected by food intake (7) or co-administration of CYP3A4 inhibitors and inducers (8, 9). Lenvatinib is rapidly and well-absorbed; it is also extensively metabolized, with predominant excretion in feces, and to a smaller extent in urine (10). The primary objectives of this study were to identify the maximum tolerated dose (MTD), dose-limiting toxicities (DLTs), and the pharmacokinetic (PK) profile of lenvatinib.…”
Section: Introductionmentioning
confidence: 99%